A novel benzimidazole derivative binds to the DNA minor groove and induces apoptosis in leukemic cells. Issue 113 (30th October 2015) - Hegde, Mahesh; Sharath Kumar, Kothanahally S.; Thomas, Elizabeth; Ananda, Hanumappa; Raghavan, Sathees C.; Rangappa, Kanchugarakoppal S.
Abstract : In the present study, we have synthesized various benzimidazole derivatives, evaluated their potential to act as DNA minor groove binder and tested their chemotherapeutic efficacy. Abstract : DNA minor groove binders are an important class of chemotherapeutic agents. These small molecule inhibitors interfere with various cellular processes like DNA replication and transcription. Several benzimidazole derivatives showed affinity towards the DNA minor groove. In this study we show the synthesis and biological studies of a novel benzimidazole derivative (MH1 ), that inhibits topoisomerase II activity and in vitro transcription. UV-visible and fluorescence spectroscopic methods in conjunction with Hoechst displacement assay demonstrate thatMH1 binds to DNA at the minor groove. Cytotoxic studies showed that leukemic cells are more sensitive toMH1 compared to cancer cells of epithelial origin. Further, we find thatMH1 treatment leads to cell cycle arrest at G2/M, at early time points in Molt4 cells. Finally multiple cellular assays demonstrate thatMH1 treatment leads to reduction in MMP, induction of apoptosis by activating CASPASE 9 and CASPASE 3. Thus our study showsMH1, a novel DNA minor groove binder, induces cytotoxicity efficiently in leukemic cells by activating the intrinsic pathway of apoptosis.